The role of controlled dosage physical exercise in the treatment of owerweight children with asthma - Velychko, V. I.; Venger, Y. I.; Bazhora, Y. I.; Pichugina, Y. O. (Journal of Education, Health and Sport, 2016)
Velychko, V.I., Venger, Y.I., Bazhora, Y.I., Pichugina, Y.O. The role of controlled dosage physical exercise in the treatment of owerweight children with asthma. Journal of Education, Health and Sport. 2016;6(3):62-71. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.47457 http://ojs.ukw.edu.pl/index.php/johs/article/view/3422 https://pbn.nauka.gov.pl/works/719716 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.01.2016. Revised 12.02.2016. Accepted: 27.02.2016. The role of controlled dosage physical exercise in the treatment of owerweight children with asthma V.I. Velychko, Y.I. Venger, Y.I. Bazhora, Y.O. Pichugina Odessa State Medical University Abstract. The study includes 115 children aged 6 to 11 years with exogenous asthma of varying severity, with different levels of control. Children with asthma were divided into two groups according to the level of physical development: I group (60 children) with harmonic physical development and II group (55 children) overweight. It was found that overweight children who have overweight greater than (4,2 ± 0,3) there are patients with severe bronchial asthma and higher than (2,5 ± 0,2) there are children with the uncontrolled progress of the disease in comparison with a group of patients with a harmonious physical development. There were recommendations on physical exercise for overweight children of 6-11 years with moderate asthma depending on the degree of control of asthma during the major periods of rehabilitation. It is shown that the efficacy of integrated application of dosed physical exercise and lipid-lowering diet with exception of carbohydrate is 1.7 times better in comparison with using only a standard diet in addition to the basic treatment of asthma. Key words: asthma, children, overweight, physical exercise.